Pengaruh Customer Service Terhadap Loyalitas Nasabah PD. BPR NTB Bima - Syarifudin, Syarifudin; Ernawati, Sri (LPPM Universitas Mataram, 2020)
In providing services, banks certainly require all employees and personnel in it to provide the best service, especially customer service because customer service is a person who receives more complaints from customers. customer service must be able to provide the best service, so that customers feel satisfied with the services provided. The purpose of this study was to determine the effect of customer service on customer loyalty in PD. BPR NTB Bima. The approach used in this research is a quantitative approach. The study population is active PD customers. BPR NTB Bima. The sampling of this research was using accidental sampling technique. Data analysis techniques used are validity and reliability, simple linear regression analysis, correlation coefficient, coefficient of determination (R2) and t test. Data processing and analysis were performed using the Statistical Product and Service Solution (SPSS) program version 21.0. The results of this study prove that there is an influence of customer service on customer loyalty.